Penerimaan Mahasiswa Akuntansi atas Aplikasi Myob Accounting dengan Pendekatan Technology Acceptance Model - Andreuw K. Pantow; Barno Sungkowo; Esrie A. N. Limpeleh; Antonius A. Tand (Politeknik Ganesha Medan, 2021)
This study aims to analyze the effect of perceptions of use, perceived ease of use and attitudes on the behavior interest of accounting students in using the Mind Your Own Business Accounting application with the Technology Acceptance Model approach. Data collection was carried out through a survey with a questionnaire to accounting students at Politeknik Negeri Manado. Analysis of research data using Partial Least Square. The results showed that when students felt the benefits and convenience of using accounting applications for the financial reporting process, it made them have the attitude to accept the use of these applications. Furthermore, the perceived benefits of using the application and the positive attitude of students towards the use of accounting applications affect their intention to use the application. Conversely, the findings of this study do not prove the effect of ease of use of applications on the intention to use accounting applications as a means of making financial reports.